Complexos de cobre com o ligante 2CP-Bz-SMe, um derivado sulfurado da base clip-phen. Síntese, caracterização e estudos de geração de radicais e clivagem de DNA - Romo, Adolfo Ignacio Barros (2015)
Coordination compounds of copper have been invoked as major actors in processes involving the reduction of molecular oxygen, mostly with the generation of radical species whose assignment have so far not been unanimously addressed. In the present work we have joined results acquired on surface and solution to get insights on the radical oxygen species (ROS) generated by a copper(II) coordination compound containing a thioether clip-phen derivative, 1,3-bis(1,10-phenanthrolin-2-yloxy)-N-(4-(methylthio) benzyli-dene)propan-2-amine (2CP-Bz-SMe). The adsorption of the copper(II) complex on gold surface was spontaneously by simple immersion of the metallic substrate in aqueous solution of the complex. The characterization of the modified gold electrode, which was performed by electrochemistry and surface Raman spectroscopy (SERS – Surface Enhanced Raman Scattering), indicated that the adsorption occurs through the sulfur atom of the thioether fragment of the molecule. While surface plasmon resonance (SPR) and electrochemistry of the adsorbed complex indicated the formation of a dimeric Cu(I) intermediate containing molecular oxygen as bridging ligand, scanning electrochemical microscopy images (SECM) pointed for OH• radical generation. Spin trapping measurements acquired by electron paramagnetic resonance (EPR) and nuclease assays run in the presence of radical scavengers, reinforced such conclusions showing that the radical production is dependent on the amount of oxygen and H2O2. Therefore, it is reasonable to assume a catalytic mechanism involving Fenton-like reaction in which the copper(II) complex is, at first, reduced to copper(I). Accordingly, in the presence of oxygen and in acid medium, the reduced compound is oxidized by H2O2 resulting in the recovering of the parent complex and in the generation of OH• that, in turn, must be the ROS responsible for the DNA cleavage. The results obtained during the developing of this proposal were presented at the XVII Brazilian Meeting on Inorganic Chemistry and are in the final compilation stage for publication in peer-reviewed journal